Fostering Excellence in Obstetrical Surgery - Wilson RD (Dove Medical Press, 2023)
R Douglas Wilson Department of Obstetrics and Gynecology, Cumming School of Medicine University of Calgary, Calgary, Alberta, CanadaCorrespondence: R Douglas Wilson, Department of Obstetrics and Gynecology, Cumming School of Medicine University of Calgary, Alberta, Canada, Tel +1 403-470-7229, Email doug.wilson@ahs.caIntroduction: This obstetric surgery review is directed toward the common obstetrical surgeries (caesarean delivery, VBAC/TOLAC, operative vaginal delivery, placenta accreta spectrum) with evidence for quality and safety to allow for obstetrical outcome excellence.Materials and Methods: This focused scoping review has used a structured process for article identification and inclusion for each of the focused surgeries.Results: The review results provide an obstetrical surgery (OS) overview for caesarean delivery, vaginal birth after caesarean delivery and/or trial of labor after caesarean delivery, operative vaginal delivery, placenta accreta spectrum; considerations for quality and safety variance due to non-clinical human factors; quality improvement (QI) tools; OS QI implementation cohorts; implementation considering certain barriers and solutions.Conclusion: Administrative health care systems and obstetrical surgery care providers cannot afford, not to consider and implement, certain evidenced-based "bottom-up/top-down" processes for quality and safety, as the patients will demand the quality and the safety, but the lawyers should not have to enforce it.Keywords: obstetrical safety, obstetrical quality, obstetrical morbidity, caesarean delivery, vaginal birth after caesarean delivery, trial of labor after caesarean delivery, operative vaginal delivery, placenta accreta spectrum, implementation process